Job Stress and Its Relationship with Employee Morale - Mann, Nimarta; Lehal , Ritu (Gyan Management Journal, 2012)
Job stress and employee morale are, in fact, highly personalized phenomenon and can vary widely even in identical situations for different reasons. This study's chief objective, therefore, was to explore the relationship between job stress and employee morale in overall banking sector and across the three sectors of banks. To sum up, it can be said that the correlation analysis shows a strong and positive correlation between job stress and low employee morale in the overall banking sector, and also suggests that improvisation of all the ten sub variables of job stress can help to enhance employee morale.
Keywords: Job Stress; Employee Morale; Banking Sector; Employee Health; Human